(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate the application of the Ministry of Health’s quality standards for stroke treatment at Nam Dinh Provincial General Hospital. Subjects and methods: Cross-sectional descriptive study on 225 patients aged 18 years and older diagnosed with stroke and transient ischemic attack treated as inpatients at Nam Dinh Provincial General Hospital from August 2021 to July 2022. Results: The study group had an average age of 72.17 ± 11.63. The male/female ratio was 1.27:1. The quality standards 3,5,7,9,10 for stroke care at the clinical level were all fully implemented on appropriate patients. 98.2% of patients received medical care from medical staff trained in stroke management. The rate of patients who received a CT scan within 1 hour was 77.6%, within 24 hours was 79.6%; 86.7% of patients were treated at the stroke unit, 52.9% of patients received multidisciplinary rehabilitation within 72 hours with a multidisciplinary care plan according to goals within 5 days. The rate of patients who were taken directly to a place with the ability to intervene with thrombolysis upon arrival at the hospital was 84.5%; 87.9% of patients with cerebral stroke had their swallowing function assessed within 4 hours of admission. Conclusion: Stroke is more common in males than in women, rises with age, and has a 100% implementation rate for five out of ten clinical quality standards.